(E)-3-furan-2-yl-N-phenylacrylamide (PAM-4) decreases nociception and emotional manifestations of neuropathic pain in mice by α7 nicotinic acetylcholine receptor potentiation. (2nd December 2021) - Bagdas, Deniz; Sevdar, Gulce; Gul, Zulfiye; Younis, Rabha; Cavun, Sinan; Tae, Han-Shen; Ortells, Marcelo O.; Arias, Hugo R.; Gurun, Mine Sibel
ABSTRACT: Clinical intervention of pain is often accompanied by changes in affective behaviors, so both assays of affective and sensorial aspects of nociception play an important role in the development of novel analgesics. Although positive allosteric modulation (PAM) of α7 nicotinic acetylcholine receptors (nAChRs) has been recognized as a novel approach for the relief of sensorial aspects of pain, their effects on affective components of pain remain unclear. Therefore, we investigated whether PAM-4, a highly selective α7-nAChR PAM, attenuates inflammatory and neuropathic pain, as well as the concomitant depressive/anxiety comorbidities. The anti-nociceptive activity of PAM-4 was assessed in mice using the formalin test and chronic constriction injury (CCI)-induced neuropathic pain model. The anxiolytic- and antidepressant-like activity of PAM-4 was evaluated using the marble burying test and forced swimming test. Acute systemic administration of PAM-4 dose-dependently reversed formalin-induced paw licking behavior and CCI-induced mechanical allodynia without development of any motor impairment. PAM-4 reversed the decreased swimming time and number of buried marbles in CCI-treated mice, suggesting that this ligand attenuates chronic pain-induced depression-like behavior and anxiogenic-like effects. The effects of PAM-4 were inhibited by the α7-selective antagonist methyllycaconitine, indicating molecular mechanism mediated by α7-nAChRs. Indeed, electrophysiological recordings showed the PAM-4 enhances human α7 nAChRs with higher potency and efficacy compared to rat α7 nAChRs. These findings suggest that PAM-4 reduces both sensorial and affective behaviors induced by chronic pain in mice by α7-nAChR potentiation. PAM-4 deserves further investigations for the management of chronic painful conditions with comorbidities.